2015
DOI: 10.18632/oncotarget.5578
|View full text |Cite
|
Sign up to set email alerts
|

A novel anti-cancer agent Icaritin suppresses hepatocellular carcinoma initiation and malignant growth through the IL-6/Jak2/Stat3 pathway

Abstract: Tumor-initiating cell (TIC) is a subpopulation of cells in tumors that are responsible for tumor initiation and progression. Recent studies indicate that hepatocellular carcinoma-initiating cells (HCICs) confer the high malignancy, recurrence and multi-drug resistance in hepatocellular carcinoma (HCC). In this study, we found that Icaritin, a prenylflavonoid derivative from Epimedium Genus, inhibited malignant growth of HCICs. Icaritin decreased the proportion of EpCAM-positive (a HCICs marker) cells, suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
100
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(100 citation statements)
references
References 50 publications
(67 reference statements)
0
100
0
Order By: Relevance
“…For example, Wang et al revealed that LncRNA-UCA1 upregulation and miR-216b inhibition could promote the progression of HCC [36], and Lv et al showed that increased LncRNA H19 contributes to migration and invasiveness of HCC cells, which is accompanied by miR-675 downregulation [37]. STAT3 signaling promotes HCC progression through the suppression of apoptosis through the induction of [38]. Therefore, we assumed that HOST2 and the JAK2/STAT3 pathway may play an important role in HCC cell migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wang et al revealed that LncRNA-UCA1 upregulation and miR-216b inhibition could promote the progression of HCC [36], and Lv et al showed that increased LncRNA H19 contributes to migration and invasiveness of HCC cells, which is accompanied by miR-675 downregulation [37]. STAT3 signaling promotes HCC progression through the suppression of apoptosis through the induction of [38]. Therefore, we assumed that HOST2 and the JAK2/STAT3 pathway may play an important role in HCC cell migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the STAT3 pathway plays a significant role in maintaining hepatocellular carcinoma [27]. Therefore, we predicted that IL-17 might maintain the self-renewal of HepG2 cells through the STAT3 pathway.…”
Section: Resultsmentioning
confidence: 96%
“…A number of signaling pathways, including the transforming growth factor β (TGF-β)/mothers against decapentaplegic homolog (1), proto-oncogene Wnt/β-catenin (2), rat sarcoma GTPase/mitogen-activated protein kinase (MAPK) (3), phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt) (4), c-Jun N-terminal kinase (JNK)/signal transducer and activator of transcription (STAT) (5,6), hedgehog and tumor protein 53 transduction pathways, serve key roles in the pathogenesis of liver cancer. Among these signaling pathways, the TGF-β signaling pathway is one of the most important (1).…”
Section: Introductionmentioning
confidence: 99%